(untitled) (Docentes 2.0 Journal, 2024)
The interdisciplinary convergence of the Science, Technology, Engineering, Arts & Mathematics (STEAM) model not only amalgamates technical engineering skills but also incorporates art as a soft competency that injects vitality into the technical learning process. The objective was to carry out the SENA curricular analysis for the design of an adaptable STEAM Training project, strengthening competencies in basic electrical circuit analysis established in the training programs of the National Learning Service (SENA) of Colombia. The research was based on the inductive method and positivist paradigm, with a quantitative approach, non-experimental design, and descriptive type. Four curricula are analyzed; among the main findings of the analysis, a matrix of contents and learning results stands out, which integrates the curricular competencies for the design of the STEAM training project from an interdisciplinary perspective. From a perspective, the design of the training project is proposed, followed by the application, implementation, and evaluation phases.